Ways of Aesthetically Integrating Conservation Theory in an Era of Neoliberal Illusions and Post-Colonial Migration - Hiltrud Schinzel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article explores the fundamental question in conservation-restoration: for whom and why do we preserve art? The motivations for conserving cultural heritage evolve over time, influenced more by sociocultural contexts than by established theories. The concept of "care" is examined as a potential approach to refocus conservation on cultural beneficiaries and their changing needs, while also considering both the material and conceptual dimensions of artworks.The article traces the historical impact of 19th-century industrialization, which democratized access to art and transformed conservation practices, but also led to increased commodification. This commercialization altered the relationship between art, its creators, and its audience, devaluing cultural assets by reducing them to market objects.Modern collectors, often disengaged from the deep involvement once required, have shifted the responsibility for conservation to public institutions, thereby weakening collective responsibility for preserving cultural heritage. In response to these changes, the article advocates for a reevaluation of conservation practices, emphasizing the importance of restoring an ethical and aesthetic connection with artworks. This approach would ensure that artworks are transmitted not merely as marketable objects but as living heritage, rich with cultural and social significance, in a context increasingly dominated by market logic.